Analysis of Expediency to Apply LCL Model with Source of Higher Harmonics of Current While Investigating Resonance Condition of Power Supply Network - M. Pavlovsky; A. Shimansky; Z. Fialkovsky (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers a power system model of a plant with one capacitor bank and with one current source of higher harmonics for higher power factor. The laboratory research results of this system and practical application of the proposed model are given in the paper.